Resident-tourist value co-creation: The role of residents' perceived tourism impacts and life satisfaction - Lin, Zhibin; Chen, Ye; Filieri, Raffaele (Tourism management (1982), 2017)
This study aims to expand tourism value co-creation to include resident-tourist social interactions. Specifically, we aim to empirically verify the effects of residents' life satisfaction and their perceived benefits and costs of tourism development on their value co-creation with tourists. An online questionnaire survey was conducted with a sample of 380 urban residents in China. Partial Least Square structural equation modelling was adopted to analyze the data. The results show that residents' perceived economic and social-cultural benefits of tourism development have positive effects on both value co-creation and life satisfaction, while perceived costs have negative effects. Life satisfaction influences value co-creation. This study contributes to the literature by conceptualizing tourism value co-creation between tourists and residents and empirically investigating residents' participation in value co-creation in the tourism context. Moreover, we introduced broaden-and-build theory to analyze a tourism phenomenon for the first time. This study also provides important managerial implications. •Value co-creation in tourism includes resident-tourist social interactions.•Positive perceptions of tourism development encourage residents' value co-creation with tourists.•Perceived costs of tourism development are negatively related to residents' value co-creation.•Life satisfaction positively influences residents' value co-creation with tourists.